Serum uric acid to HDL-cholesterol ratio is a strong predictor of metabolic syndrome in type 2 diabetes mellitus - Kocak,M. Zahid (2019)
SUMMARY OBJECTIVE Metabolic syndrome (MS) is a clinical entity that associated with increased risk of type 2 Diabetes Mellitus (DM) and cardiovascular diseases. Serum uric acid levels are correlated MS criteria. We hypothesized whether a uric acid to HDL-cholesterol ratio (UHR) could predict diabetic regulation and presence of MS in type 2 diabetic subjects. METHODS Admissions of the subjects with type 2 DM to outpatient clinics of our institution were retrospectively analyzed. Study population grouped into well-controlled and poorly controlled diabetics according to the HbA1c level (cut off 7%) and further grouped into type 2 DM with and without MS according to the presence of MS. UHR of study groups compared. RESULTS A hundred diabetic subjects enrolled. Mean UHR was significantly lower in well-controlled diabetics (9.7 ± 3.7%) compared to poorly controlled subjects (14 ± 5.4%) (p<0.001). Median UHR of diabetics with MS (13 (6-29) %) was greater than that of the diabetics without MS (9 (3-16) %) (p<0.001). UHR greater than 11% has 77% sensitivity and 60% specifity in predicting worse diabetic control (AUC: 0.752, p<0.001) and a UHR greater than 10.6% has 83% sensitivity and 71% specifity in predicting MS (AUC: 0.839, p<0.001). Sensitivity and specifity of UHR in predicting MS were better than most of the sensitivities and specifities of the five criteria of MS. CONCLUSION We suggest utilization of UHR in diagnosis of MS as a novel criteria. Nevertheless, prospective studies with larger population may make a better scientific evidence in that issue.